Pengaruh Penyajian Laporan Keuangan Dan Aksesibilitas Terhadap Akuntabilitas Pengelolaan Laporan Keuangan Daerah Kota Kupang - Ala, Helda Marlin; Lerrick, Yudith F. (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2024)
This research raises the issue of the influence of financial report presentation and accessibility on the accountability of regional financial management in Kupang City. This research aims to examine: (1) The effect of financial report presentation on regional financial management accountability (2) The effect of accessibility on regional financial management accountability (3) The effect of financial report presentation and accessibility on regional financial management accountability. The research method used is purposive sampling, with primary data sources. The object of this research is the Kupang City Regional Financial and Asset Agency, which is located on Jl. S. K. Lerik No. 1, Kelapa Lima, Kupang City, East Nusa Tenggara, consisting of 35 respondents. Data collection through direct observation and questionnaire surveys to respondents. Data analysis uses quantitative methods using descriptive statistical tests and classical assumption tests, as well as hypothesis testing using SPSS 25. The research results reveal that the presentation of financial reports has a positive and significant effect on regional financial management accountability, this indicates that the better the presentation of regional financial reports, the better the accountability of regional financial management. There is a positive and significant influence of accessibility on regional financial management accountability, this shows that increasing accessibility has had a direct impact on increasing accountability in regional financial management. The results of simultaneous testing with the F test show that both the presentation of financial reports and accessibility have a positive effect on the accountability of regional financial management